Solid Waste Disposal Management in A Residential Complex of a Defense Establishment- A Modern Approach - Jagdamba Dixit; Anil Kumar Dixit; Singh Narendra (Medsci Publications, 2014)
Introduction: A study on "Solid Waste Disposal Management" was conducted as an AFMRC project at a flying defence establishment to design and implement newer scientific methods and techniques. The objective of the project was to reduce, reuse and recycle the generated waste for more eco-friendly and safe environment to live and fly. Material and methods: A new module making use of newer methods and techniques was designed and implemented. Solid waste was collected in two segregated forms viz. biodegradable and non biodegradable at the household level and was transported in separate containers to the segregation site. Biodegradable waste was introduced into vermiculture ponds and non biodegradable waste was segregated into different components. At the end of follow up period of one year, a noticeable difference was observed in the hygienic conditions in the houses and surrounding environment. Results: On an average a family produces about 556 gm of total solid waste, comprising of 419 gm of non-biodegradable and 137 gm of biodegradable components.Biodegradable waste was reduced to a very great extent and changed into highly fertile manure. Non recyclable items were disposed off by dumping, while recyclable items were segregated and reduced by crushing, shredding or cutting and were finally sold to the vendors to generate cash. Conclusion: The AFMRC project "Solid Waste Disposal Management" has been found useful in controlling the problems of environmental sanitation. Similar projects may be undertaken at large scale to reduce, reuse and recycle the generated waste.